From yeast to human: exploring the comparative biology of methionine restriction in extending eukaryotic life span. Issue 1 (January 2016) - McIsaac, R. Scott; Lewis, Kaitlyn N.; Gibney, Patrick A.; Buffenstein, Rochelle
Abstract : Methionine restriction is a widely reported intervention for increasing life span in several model organisms. Low circulating levels of methionine are evident in the long‐lived naked mole‐rat, suggesting that it naturally presents with a life‐extending phenotype akin to that observed in methionine‐restricted animals. Similarly, long‐lived dwarf mice also appear to have altered methionine metabolism. The mechanisms underlying methionine‐restriction effects on life‐span extension, however, remain unknown, as do their potential connections with caloric restriction, another well‐established intervention for prolonging life span. Paradoxically, methionine is enriched in proteins expressed in mitochondria and may itself serve an important role in the detoxification of reactive oxygen species and may thereby contribute to delayed aging. Collectively, we highlight the evidence that modulation of the methionine metabolic network can extend life span—from yeast to humans—and explore the evidence that sulfur amino acids and the concomitant transsulfuration pathway play a privileged role in this regard. However, systematic studies in single organisms (particularly those that exhibit extreme longevity) are still required to distinguish the fundamental principles concerning the role of methionine and other amino acids in regulating life span.